Raising funds in the secondary markets a brief review of the academic research related to Seasoned Equity Offers (SEOs) - Singh, Ajai (Henry Stewart Talks, 2014)
Additional equity capital in secondary markets, Seasoned equity offers (SEO), Market timing/windows of opportunity, Investment-based financing needs, Two primary methods of issuing equity publicly, Accelerated shelf offers vs. fully-marketed offers, The fully-marketed SEO process, Offer size, offer price & offer price discount, Primary objective of the investment banker, Amended proceeds hypothesis, Two types of firm, The offer date, expected offer size and final offer size, Separate and additional indication to the market, Improved SEOs vs. Regular SEOs, Mimicry (Fooling clients with amended proceeds), Dollar proceeds from filing to offer, Stock price response, Cross-sectional analysis of offer-date returns, Calendar-time regressions: Improved & regular SEOs, WLS regression approach, Fama-MacBeth regression, Long-run stock return performance & metrics, Changes in operating performance & investments, Institutional investor demand for SEOs